KARAKTERISTIK KEMAMPUAN BERFIKIR KREATIF MATEMATIKA SISWA KELAS VII SMPN 4 GERUNG PADA MATERI SEGI TIGA DAN SEGIEMPAT TAHUN AJARAN 2024/2025 - Damayanti, Eka Rahayu; Arjudin; Turmuzi, Muhammmad; Sarjana, Ketut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract The ability to think creatively mathematically is an ability that students need to have to analyze mathematical problems from various points of view and then solve them with the ability to have many solutions and give birth to creative ideas and lots of ideas. The aim of the research is to describe the creative thinking abilities in mathematics of SMPN 4 Gerung students and which creative thinking abilities SMPN 4 Gerung students have. that students' creative thinking abilities in solving mathematics problems in class VIII at SMP Negeri 4 Gerung in the 2023/2024 academic year are generally dominant at level 1 (Less creative) at 37.5%. Then followed by students who were at level 3 (very creative) with 28.125%. Next, students who were at level 2 (creative) were 21.875% and finally students who were at level 0 (not creative) were 12.5%. So it can be concluded that the level of creative thinking of class VIII students at SMPN 4 Gerung is at level 1 (less creative).